1979
DOI: 10.1007/bf00413321
|View full text |Cite
|
Sign up to set email alerts
|

The influence of clonidine on intraocular pressure after topical application to the eyes of anesthetized cats

Abstract: Clonidine was topically applied to the right eye of anesthetized cats. Unilateral administration induced a fall in intraocular pressure (IOP) in both eyes. This effect is not secondary to the slight fall in arterial blood pressure. Distribution experiments with 14C-clonidine revealed that only minor or negligible amounts of clonidine could be demonstrated in the contralateral eye. The concentrations of the labeled drug determined in the brain after topical application are sufficient to explain the bilateral de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This fellow eye effect may be due to a central neural action similar to that observed with topical clonidine. [6][7][8][9] This contralateral effect may make it more difficult to determine the effica¬ cy of IOP lowering by apraclonidine if a one-eye therapeutic trial is used in eyes with glaucoma.14 Topical 1% apraclonidine hydro¬ chloride caused no significant change in the facility of aqueous outflow. These tonographic results are similar to those involving topical clonidine.8 Apraclonidine decreases aqueous hu¬ mor flow approximately 30% in fluorophotometric studies according to R. F. Brubaker, MD (written commu¬ nication, Aug 31, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…This fellow eye effect may be due to a central neural action similar to that observed with topical clonidine. [6][7][8][9] This contralateral effect may make it more difficult to determine the effica¬ cy of IOP lowering by apraclonidine if a one-eye therapeutic trial is used in eyes with glaucoma.14 Topical 1% apraclonidine hydro¬ chloride caused no significant change in the facility of aqueous outflow. These tonographic results are similar to those involving topical clonidine.8 Apraclonidine decreases aqueous hu¬ mor flow approximately 30% in fluorophotometric studies according to R. F. Brubaker, MD (written commu¬ nication, Aug 31, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of selective ct2-receptor agonists on intraocular pressure in the conscious rabbit was initially reported by Innemee et al (20,21). Stimulation of the 0.2-subtype with B-HT 920 or 933, caused a marked and dose-dependent ocular hypotensive response.…”
Section: Discussionmentioning
confidence: 96%
“…This effect was blocked by the ot2-adrenergic antagonist, yohimbine. Since this initial observation, several other selective cx2-adrenergic agonists have been shown to reduce IOP in rabbits (6,7), cats (18,20) and monkeys (6), and a few promising compounds have entered the clinical development phase, apraclonidine and brimonidine (UK 14,304). These agents have demonstrated to safely and effectiviely lower IOP in normotensive volunteers as well as in glaucoma patients (22,23).…”
Section: Discussionmentioning
confidence: 98%
“…It has been postulated that this inhibitory activity can be initiated at sites within the brain (5,6) and/or on peripheral noradrenergic neurons (5,7). Recently, it was suggested that dopaminergic agonists may produce depression of sympathetic neuronal function by an action on prejunctional a2-adrenoceptors (8), although results indicate the functional presence of DA2 receptors in the eyes of cats, rabbits, and monkeys (2,4,9) as well as humans (10,11).…”
Section: Introductionmentioning
confidence: 97%